An Internet of Things (IoT)-Based Automatic Watering System Using Sprinklers for Water Efficiency in Kampung Baru Subdistrict - Rahmat Bagus Febrian; Sindi Nisja Waruwu; Rohana Telaumbanua; Nurul Istiqamah; Vera Azikra Yorisa A; Evi Febriyanti Sitorus; Yoga Kurnia Wira Tambega; Dian Lestari Saputri; Ayu Saputri; Amaliya Tuti Anggraeni; Hamdany Maulana; Ridho Tri Rokhandi; M Indra Rizki Pratama; Deri Handrian Putra; Muhammad Robby Farhan (PT. TAKAZA INNOVATIX LABS, 2026)
Abstract:Agriculture in Kampung Baru Village faces water management challenges due to labor-intensive and inefficient manual irrigation methods, especially on the 3.25 ha horticultural land of the Mekar Tani farmer group. This community service aims to implement an IoT-based automatic watering system using sprinklers with an ESP32 microcontroller and the Thinger.io application to improve water efficiency. Using action research with a participatory community development approach, a purposive sample of 20 farmers from five farmer groups (7,421 people) was taken. Instruments including soil moisture sensors, solenoid valves, sprinklers, and ESP32 integrated monitoring applications were analyzed using qualitative-quantitative descriptive techniques and water efficiency formulas. The results show significant water savings, soil moisture stability, optimal growth of horticultural crops (lettuce, mustard greens, kale, spinach, chilies, tomatoes), and increased farmer capacity through training. In conclusion, the IoT system provides a sustainable smart farming model that can be replicated in rural Jambi for food security.